Synthesis and biological evaluation of 2.4 nm thiolate-protected gold nanoparticles conjugated to Cetuximab for targeting glioblastoma cancer cells via the EGFR. (21st February 2019) - Groysbeck, Nadja; Stoessel, Audrey; Donzeau, Mariel; da Silva, Elisabete Cruz; Lehmann, Maxime; Strub, Jean-Marc; Cianferani, Sarah; Dembélé, Kassiogé; Zuber, Guy
Abstract: Therapeutic monoclonal antibodies benefit to patients and the conjugation to gold nanoparticles (AuNPs) might bring additional activities to these macromolecules. However, the behavior of the conjugate will largely depend on the bulkiness of the AuNP and small sizes are moreover preferable for diffusion. Water-soluble thiolate-protected AuNPs having diameters of 2–3 nm can be synthesized with narrow polydispersity and can selectively react with incoming organic thiols via a SN 2-like mechanism. We therefore synthesized a mixed thionitrobenzoic acid-, thioaminobenzoic acid-monolayered AuNP of 2.4 nm in diameter and developed a site-selective conjugation strategy to link the AuNP to Cetuximab, an anti-epidermal growth factor receptor (EGFR) antibody used in clinic. The water-soluble 80 kDa AuNP was fully characterized and then reacted to the hinge area of Cetuximab, which was selectively reduced using mild concentration of TCEP. The conjugation proceeded smoothly and could be analyzed by polyacrylamide gel electrophoresis, indicating the formation of a 1:1 AuNP-IgG conjugate as the main product. When added to EGFR expressing glioblastoma cells, the AuNP-Cetuximab conjugate selectively bound to the cell surface receptor, inhibited EGFR autophosphorylation and entered into endosomes like Cetuximab. Altogether, we describe a simple and robust protocol for a site-directed conjugation of a thiolate-protected AuNP to Cetuximab, which could be easily monitored, thereby allowing to assess the quality of the product formation. The conjugated 2.4 nm AuNP did not majorly affect the biological behavior of Cetuximab, but provided it with the electronic properties of the AuNP. This offers the ability to detect the tagged antibody and opens application for targeted cancer radiotherapy.